2013
DOI: 10.1080/01635581.2013.789118
|View full text |Cite
|
Sign up to set email alerts
|

Low-Glucose Conditions of Tumor Microenvironment Enhance Cytotoxicity of Tetrathiomolybdate to Neuroblastoma Cells

Abstract: Growth of tumor cells depends on sufficient supply of fermentable substrate, such as glucose. This provokes development of new anticancer therapies based on dietary restrictions. However, some tumor cells can lower their glucose dependency and activate processes of ATP formation/saving to retain viability even in limited glucose supply. In addition, tumor cells often lose sensitivity to many conventional anticancer drugs in the low-glucose conditions. Thus, development of the drugs effectively killing the tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Using neuroblastoma cells (SH-SY5Y and SK-N-BE) Navratilova et al demonstrated that tetrathiomolybdate (TMD), a drug that exhibits anti-angiogenic and tumor-suppressing effects increased glucose uptake, production of lactate, and activation of Akt and AMPK signaling pathways as angiogenic “escape strategies” of NB cells under low glucose conditions 125 . Under low glucose conditions, these effects lead to a significant decrease of intracellular ATP supply and apoptosis.…”
Section: Clinical Implications Of the Tumor Macroenviromentmentioning
confidence: 99%
“…Using neuroblastoma cells (SH-SY5Y and SK-N-BE) Navratilova et al demonstrated that tetrathiomolybdate (TMD), a drug that exhibits anti-angiogenic and tumor-suppressing effects increased glucose uptake, production of lactate, and activation of Akt and AMPK signaling pathways as angiogenic “escape strategies” of NB cells under low glucose conditions 125 . Under low glucose conditions, these effects lead to a significant decrease of intracellular ATP supply and apoptosis.…”
Section: Clinical Implications Of the Tumor Macroenviromentmentioning
confidence: 99%
“…The contribution of the TME to this effect has not been well explored and is thus poorly understood. There is some suggestion that dietary restriction leading toward low glucose concentration may inhibit the Warburg effect and increase cytotoxicity in neuroblastoma cell lines [81]. …”
Section: Role Of the Tme In The Hallmarks Of Neuroblastomamentioning
confidence: 99%
“…Usually, Hsp72 is upregulated in response to stress stimuli, and is thought to enhance heat shock tolerance and restore systemic balance [6]. Following extrinsic and intrinsic stressors, including cytotoxic drugs, UV irradiation, low pH [7], limited glucose [8], and hypoxia [9], tumour cells express uncommonly high levels of both Hsp72 and Hsc70 constitutively [10]. Increased expression of Hsp72 and Hsc70 has been implicated in tumour pro-survival through modulation of critical cell-signalling pathways that control cell fate.…”
Section: Introductionmentioning
confidence: 99%